Forced vital capacity (FVC), peaked expiratory flow rate (PEFR), are additional parameters in the assessment of the reversibility test. - Abd Ali, Mustafa N.; Jasim, Ahmed H.; Nassr, Abdulrasool N.; Kaddish, Monqith A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Spirometry is an important test performed in patients expect to have airway obstruction, assessment of intense reaction to inhalers (the trial of reversibility of airway blockade) is a normally utilized technique in clinical and academic studies. The consequences of this test are utilized to make choices on treatment, consideration, exclusion from diagnosis and other research think about, and for analytic marking [asthma versus chronic obstructive airway disease (COPD)]. Usually, the (FEV1) or (FVC) standards before and after giving of the bronchodilator are compared and the adjustment is processed to distinguish variations from the norm in lung volumes and air flow.Objective: The aim of this study was to investigate the effectiveness of FVC and PEFR as further constraints to evaluate bronchodilator reaction in asthmatic peoples with severe or moderate airflow blockade.Patients and methods: This study is cross sectional study performed in Baghdad teaching hospital where one hundred patient were enrolled in this study patients were detected with asthma and confirm airway blockade according to (GINA) guide lines. The pulmonary function for all members was investigated with a convenient spirometer (spiro-lab3 Spirometer) as stated by those measures from claiming American thoracic particular social order, The mean and standard deviation results of the predicted% values pulmonary function test were also used for comparisons were measured by t-test. A p-value of ≤ 0.05 considered to be significant statistically.Results: The post bronchodilator (post –BD) results of FVC, PEFR are greater than pre- bronchodilator where are statistically significant P value = 0.00. the amount of the changes of FVC post (BD) was more than 400ml from pre (BD) and the amount of the changes of PEFR post (BD) more than 1000ml from the pre (BD) both were p-value = 0.00.Conclusion: The asthmatic patients with moderate and severe airway obstruction, we observed that FVC and PEFR is a valuable important limit to FEV1 to evaluate reversibility reactionKeyword: forced vital capacity(FVC), peaked expiratory flow rate (PEFR), spirometry and forced expiratory volume in 1st second (FEV1).